Effects of Switching from Insulin Glargine or Detemir to Insulin Degludec in Patients with Type 1 Diabetes Mellitus - Kusunoki, Yoshiki (Springer Healthcare, 2013)
INTRODUCTION: Insulin degludec is a new, ultra-long-acting basal insulin. The aim of this study was to analyze the changes of basal insulin dose and blood glucose profile in basal–bolus therapy of type 1 diabetes mellitus (T1DM) at the switching of basal insulin from insulin glargine or detemir to insulin degludec. METHODS: Sixteen patients with T1DM were enrolled. The patients underwent continuous glucose monitoring before and after the switching of insulin glargine or detemir to degludec. Ten patients treated with insulin glargine or detemir twice daily, were switched to insulin degludec with 80–90% of the prior insulin dose. The remaining six patients treated with insulin glargine once daily, were switched to insulin degludec without down titration. The changes of daily insulin dose and glycated hemoglobin (HbA1c) were also examined for 12 weeks after switching to insulin degludec. RESULTS: In the patients switched from twice-daily basal insulin, no significant difference was found between before and after switching in the blood glucose profile. In the once-daily group, blood glucose levels showed a tendency to decrease after switching to the degludec treatment. During the study period, total daily insulin dose (TDD) and total daily basal insulin dose (TBD) decreased significantly in the twice-daily group, and TDD and TBD showed a tendency to decrease after switching to degludec in the once-daily group. In both groups, the changes of HbA1c were not significantly different. CONCLUSION: It is possible to achieve similar glycemic control with once-daily injection and lower doses of insulin degludec in patients with T1DM who have been treated with insulin glargine or detemir.